'Dirt and the child': a textual and visual exploration of children's physical engagement with the urban and the natural world. Issue 4 (3rd July 2020) - Grosvenor, Ian; Myers, Kevin
ABSTRACT: In the nineteenth century city child rescuers developed 'a taxonomy of space' in which geography determined destiny. The privatised spaces of the middle classes were contrasted with the 'dirt, disease and delinquency' of the slums. Yet at the same time as 'dirt' was viewed as 'destructive' and proof of urban neglect it was also accepted in the form of rural soil to be 'fertile' and central to helping sustain life. This paper explores the emergence of this spatial taxonomy of destiny and its associated vocabulary of descriptors; it documents the visual duality of 'dirt' as a signifier of both 'risk' and of the 'pastoral'; and finally it examines some of the ways in which activists in one city sought in the twentieth century to bridge the divide and bring 'nature' into the city.